Urban governance in Bangladesh and Pakistan - Islam, Nazrul, 1941-; Khan, Mohammad Mohabbat, 1949-; University of Dhaka. Centre for Urban Studies (Dhaka : Centre for Urban Studies, 1997)
Contributed articles.
Includes bibliographical references.
Keywords: Land use, Urban -- Bangladesh; City planning -- Bangladesh; Land use -- Environmental aspects -- Bangladesh